An equivalent error based stochastic model for improving the accuracy prediction in 3-axis FXYZ coordinate measuring machines. (September 2021) - Franco, P.; Jodar, J.
Highlights: The equivalent error (EE) is defined as a new error index for CMM modelling. An EE-based stochastic model is proposed for CMM measuring accuracy evaluation. This model serves to predict the effect of the distinct error sources of CMMs. The proposed model is oriented to 3-axis CMMs with FXYZ configuration. The EE-based model is validated by its comparison with a traditional method. Abstract: The analysis of the measuring accuracy of coordinate measuring machines (CMMs), requires a profound knowledge about the existing error sources. In this work a new error index named equivalent error (EE) was defined to facilitate the evaluation of CMM performance, and an EE-based stochastic model for predicting the CMM measuring accuracy was proposed. The present study was focused on the analysis of position, straightness and part errors, and 3-axis CMMs with FXYZ structural configuration. Both a traditional method with separate error sources and this new EE-based model have been applied. The EE-based model was proved to enhance the modelling of CMM measuring accuracy from the position, straightness and part errors, and to be helpful for industrial applications such as the dimensional verification of manufactured products. A remarkable improvement of a 19.69% was achieved in the linear modelling of CMM performance by the EE-based model in comparison with a traditional method.